520 Male dairy calf transportation welfare and market value in British Columbia. (7th December 2018) - Wilson, D; Stojkov, J; Fraser, D
Abstract: Male dairy calves are typically sold and transported to grower operations at a young age when they are vulnerable to health and welfare problems. We assessed male dairy calf health and immune status at the farm of origin before transportation and determined how health measures correlated to calf price. From October 2017 to March 2018, calves (n=646) from 18 dairy farms in British Columbia were assessed within 24 hours before shipping. Data included birth date, heart girth, as well as evidence of diarrhea, pneumonia, and navel disease. Serum total protein was estimated by optical refractometry within 7 days of age taking a cut-off value of < 5.2 g/dL as an indicator of failure of transfer of passive immunity. Price was recorded for 1688 calves sold at one BC auction market including the 126 calves of known health status. Descriptive statistics were calculated for each health measure and a general linear model was used to assess how health measures influenced calf price. Calves were sold at 6.7 ± 0.4 d (mean ± SE, range of 3 to 41 days). Calf health varied greatly between farms, with 17% of calves (0–43%) showing diarrhea, 2% (0–20%) with clinical signs of pneumonia, and 9% (0–19%) with navel disease. Failure of transfer of passive immunity was detected in 13% calves, ranging from 0 to 26%. Mean calf price was 127 ± 2 (mean ± SE) but 11% of calves sold for ≤ 10 and 3% were deemed unsaleable. The price at auction was positively correlated with calf heart girth (R2=0.56, P < 0.001), but not well correlated with other health measures. In summary, calf health and immune status were highly variable before transportation; improvements could increase the market value of calves and enhance their welfare as they transition from the dairy to calf growing operations.